Sistem Penganalisis Sintaks Otomatis dengan Metode Generalized-LR Parsing - Rila Mandala; Antonius Sigit; Rinaldi Munir; Harlili Harlili (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
The main problem of difficulties in natural language processing is ambiguity. Almostin all level of natural language processing there are ambiguities, including in syntax level.LR-Parser is an efficient method that often be used in developing a programming languagecompiler for parsing, but unfortunately it can not be used for parsing natural languageprocessing because it can not handle the ambiguity. This paper uses Generalized-LR Parsing,a modified-LR-Parsing method that can handle ambiguity, for parsing a sentence in BahasaIndonesia. Generalized-LR Parsing use a graph-structured stack to cope the ambigutiyproblem. It can successfully produce all parsing-trees for an ambiguous sentence in BahasaIndonesia.Keywords: natural language processing, syntax analysis, ambiguity, Generalized LRParsing,parsing-tree